The Impact of Air and Water Pollution on Biodiversity in Urban Ecosystems in the City of Tikrit - Mohammed, Hiba Hamad (American Journal of Biodiversity, 2025)
The study was initiated with sampling surface water from several sites in the city of Tikrit to assess the environmental status of the surface water, water quality analysis irrespective of the environment, and the environmental water pollution in the local ecosystem. Physical and Chemical analysis of the water showed that the water tended to become acidic, where the PH value was recorded below the minimum allowable. This meant indicators such as organic matter decay and sewage leaking. Turbidity levels were high and outside the limits, which indicates the presence of a large amount of suspended particles such as bacteria, clay and algae, clear signs of organic pollution and the possible contamination of microbes. Results also showed high electrical conductivity indicating presence of high concentration of dissolved salts, presumably result from runoff along with industrial waste or fertilizers. These salts overwhelm water quality and adversely affect biodiversity. It turned out that dissolved oxygen (DO) concentration was very low, indicating intense organic breakdown using oxygen up and contributing to an aquatic habitat that does not welcome aquatic life. Nutrient analysis revealed high concentrations of nitrates 28 mg/L, phosphates (2.1 mg/L), and ammonium (1.6 mg/L) that are strong indicators of organic pollution that is caused by sewage release or intensive use of fertilizers. These nutrients contribute to eutrophication leading to excessive growth of algae, reducing the oxygen levels and directly endangering aquatic life. As for the heavy metals, they found high and dangerous levels, where lead concentration was 0.12 mg/L, and is 12 times higher than the acceptable limit, and mercury and cadmium amounted to 0.005 and 0.015 mg/L respectively. All of them are over international standards, toxic and cumulative, which is a real threat to public health, especially children and pregnant women. The city’s air environment was also not in good condition with high PM2.5 and PM10 concentration were also reported in the middle of the day especially due to traffic congestion and industrial activities contributing to high air pollution leading to poor air quality and health of the residents. The study also demonstrated the clear decrease in biodiversity, with the less polluted placing recording higher diversity in flora, insects and birds, with many species disappearing in the heavily polluted areas, in particular, sensitive organisms such as amphibians. All these are summed results of a condition of robbing in the process of gradual environmental destruction, because the ecosystems have lost the ability to self-renew and drastically process the pollution natural way. Organic pollution metallic Air pollution has reached alarming levels which need to be fixed immediately through improving the sewage infrastructure, regulating the industries and checking the pollution regularly in water, air to keep the population and environment safe from pollution.